Desain dan Uji Coba Weblog Kimia Kontekstual untuk Mendukung Literasi Sains Siswa pada Materi Larutan Elektrolit dan Non Elektrolit - Kurniawati, Yenni; Riady, AD; Hendri, Jhon (Lembaga Intelektual Muda (LIM) Maluku, 2024)
This research aims to develop contextual chemistry weblog-based learning media on electrolyte and non-electrolyte solution material to improve students' scientific literacy. This media was designed using the Borg & Gall development model, through the stages of needs analysis, planning, development, validation, testing and revision. The validation process involves media design experts, material experts and language experts to evaluate aspects of appearance, content and language. The trial was carried out at SMA IT Al-Ittihad Pekanbaru involving one chemistry teacher and 10 class X science students. The research results show that this learning media has a very good level of validity with an average score of 89.16% from expert validation. The practicality of the media by teachers was also rated very high with a score of 92%, confirming ease of use, suitability of content to the curriculum, and clarity of language. Student responses to the media showed that 90% of students felt this media was interesting and helped understand the material, while 80% of students thought the design and interactivity of the media supported independent learning